National Ambulatory Medical Care Survey, 1991 ([Verlag nicht ermittelbar], 1995)
The National Ambulatory Medical Care Survey (NAMCS) provides data from samples of patient records selected from a national sample of office-based physicians. These national estimates describe the utilization of ambulatory medical care services in the United States. In 1991, there were 33,795 patient records provided by 1,354 doctors who participated in the survey. The survey obtains information on the age, race, and sex of the patient, and on physician characteristics such as geographic location and specialization. Data describing the nature of the office visit include the expected source of payment, patient's problem, prior visit status, referral status, physician's diagnoses, diagnostic and therapeutic services provided, and disposition and duration of the visit. Other variables cover drugs/medications ordered, administered, or provided during office visits, such as medication code, generic name and code, brand name, entry status, prescription status, composition status, and related ingredient codes.